The Impact of Information and Communication Technology on the Academic Achievement of Creative Art Students in Secondary Schools - Adeloye, Adebayo Abiodun; Kayode, Tope Dare; Ariyo, Emmanuel; Jeje, Omotunde Matthew (NIU Journal of Humanities, 2023)
This study assessed the effects ICT tools on academic performance of creative arts students in selected Nigerian secondary schools in Ondo state. The study adopted pre-test post-test quasi experimental research design. One hundred and sixty (160) creative arts students were purposively selected from four schools in Akure south local government area of Ondo state based on gender and academic track records. The selected students were divided into two groups; the control group and the experimental group. One objective and two research hypotheses were generated for the study. Data was gathered from both primary and secondary sources. A set of teacher made text and ICT Instructional Packages such as instructional videos were used for data collection. Experimental group was taught using ICT Instructional packages while the control group were exposed to conventional method of teaching. The schools were selected based on the availability of ICT gadgets and access to power supply. The study revealed that students taught with the ICT Instructional packages performed significantly better than those taught using conventional teaching method. The data collected was analyzed using descriptive and inferential statistics. Independent sample t-test was used to test the hypotheses. The result also shows that the use of ICT based Instructional packages in teaching creative arts is not significantly affected by the gender of the students. It was therefore recommended that the application of ICT-based instructional strategy should be encouraged as an effective tool for teaching and learning in secondary schools in Nigeria. The government and private directors of schools are also encouraged to provide more ICT gadgets to schools in order to make teaching and learning more effective. Keywords: ICT, Art, Design, Secondary school and Academic performance.